Tracheostomy in the COVID-19 era: global and multidisciplinary guidance. Issue 7 (July 2020) - McGrath, Brendan A; Brenner, Michael J; Warrillow, Stephen J; Pandian, Vinciya; Arora, Asit; Cameron, Tanis S; Añon, José Manuel; Hernández Martínez, Gonzalo; Truog, Robert D; Block, Susan D; Lui, Grace C Y; McDonald, Christine; et al.
Summary: Global health care is experiencing an unprecedented surge in the number of critically ill patients who require mechanical ventilation due to the COVID-19 pandemic. The requirement for relatively long periods of ventilation in those who survive means that many are considered for tracheostomy to free patients from ventilatory support and maximise scarce resources. COVID-19 provides unique challenges for tracheostomy care: health-care workers need to safely undertake tracheostomy procedures and manage patients afterwards, minimising risks of nosocomial transmission and compromises in the quality of care. Conflicting recommendations exist about case selection, the timing and performance of tracheostomy, and the subsequent management of patients. In response, we convened an international working group of individuals with relevant expertise in tracheostomy. We did a literature and internet search for reports of research pertaining to tracheostomy during the COVID-19 pandemic, supplemented by sources comprising statements and guidance on tracheostomy care. By synthesising early experiences from countries that have managed a surge in patient numbers, emerging virological data, and international, multidisciplinary expert opinion, we aim to provide consensus guidelines and recommendations on the conduct and management of tracheostomy during the COVID-19 pandemic.